Intermediate snapshot on the insertion reaction of isocyanates into the Zn–Cp* bond of dizincocene Cp*2Zn2. Issue 61 (30th June 2020) - Li, Bin; Wölper, Christoph; Huse, Kevin; Schulz, Stephan
Abstract : Heteroleptic Zn(i ) complexes Cp*Zn–Zn(N(R)C(Cp*)O) with η 4 -coordinated tethered Cp* ligand represent snapshots of isocyanate insertion reactions into Zn–Cp* bonds. Their bonding nature was analysed by single crystal X-ray diffraction and computational calculations. Abstract : Heteroleptic Zn(i ) complexes Cp*Zn–Zn(N(R)C(Cp*)O) (R = Dipp = 2, 6-i-Pr2 -C6 H3 2, t -Bu 3 ) with unsymmetrically η 4 -coordinated Cp* substituents represent snapshots of the insertion reaction of RNCO into the Zn–Cp* bond of Cp*2 Zn2 1 . The bonding situation in 2 and 3, which represent the first Zn(i ) olefin complexes, was evaluated by computational calculation and further compared to other Zn(i ) complexes.